PENGEMBANGAN E-MODUL BERBASIS KONTEKSTUAL SEBAGAI PENDUKUNG PEMBELAJARAN JARAK JAUH KELAS X IPS - Fitriyah Dwi Febrian; Norida Canda Sakti (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2021)
This study aimed to develop contextual-based E-Module learning media by testing the level of feasibility, student responses, and students' comprehension. This study used a type of R&D development research with a 4D model by Thiagarajan with four stages, namely defining, designing, developing, and spreading. The trial design used was the One Group Pretest- Posttest Design with 20 research subjects. Contextual-based E-Module was found to be very feasible to be used as a learning media with following aspect such as results of material experts by 99,44%, linguist validation of 78%, validation of media experts by 94,36%, and expert evaluation validation of 94.36%. The students' response result were 94.5% which was categorized as very feasible. Students' comprehension was measured by a gain score test and obtained a result of 0.375 so that it could be stated that there was an increase in students' understanding. This shows that contextual-based E- Module learning media is suitable for use in learning economic subjects to increase students' comprehension.